Retrograde Transvenous Obliteration of Gastric Varices using Sodium Tetradecyl Sulphate: Technical Considerations and Results from a Single Institution Retrospective Study - Khera, Pushpinder S.; Garg, Pawan K.; Tiwari, Sarbesh; Bhargava, Narendra; Yadav, Taruna; Sureka, Binit; Ghosh, Tushar; Babu, Santhosh; Dadhich, Sunil; Singh, Surjit (Journal of Clinical Interventional Radiology ISVIR, 2021)
Introduction Retrograde transvenous obliteration (RTO) with the assistance of a balloon (BRTO) or a vascular plug (PARTO) is an established method for treating gastric varices (GVs) secondary to portal hypertension. Most of the available studies on RTO have used lipiodol along with sclerosing agents like ethanolamine oleate or sodium tetradecyl sulfate (STS). We evaluated the safety and efficacy of RTO for treating GVs using STS as a sclerosant without lipiodol.Materials and Methods Sixteen patients (nine men, age range 16–74 years) were included in this retrospective study. Twelve patients presented with acute bleeding, two with chronic bleeding, one with large varices without bleeding, and one with refractory hepatic encephalopathy (HE). BRTO was attempted in 14 patients and PARTO in 2 patients. The technical and clinical success and complications of RTO were studied.Results The RTO procedure was technically successful in 14 (14/16, 87.5%) patients, with 13 (13/14, 93%) obtaining clinical success. One patient died due to the early recurrence of bleeding. Three patients had minor intraprocedural complications.Conclusion Retrograde gastric variceal obliteration using STS is safe and technically feasible with high technical and clinical success and low complication rate.
Keywords: bleeding gastric varices; retrograde transvenous obliteration; balloon-occluded retrograde transvenous obliteration; plug-assisted retrograde transvenous obliteration; gastrorenal shunt; hepatic encephalopathy; sodium tetradecyl sulfate